Still dirty: the effect of global risks and development on foreign direct investment inflow - Kaukab, M. Elfan (Business: Theory and Practice, 2024)
There needs to be more research on the global risks and developmental determinants of foreign direct investment inflow with green investment campaigns. This article presents new evidence covering 116 countries (2018–2020) using least squares regression. We show that ceteris paribus, higher perceived environmental and geopolitical risks are more likely to increase foreign direct investment. We also find that lower business environment, safety and security, and environmental sustainability increase foreign direct investment inflow. Meanwhile, foreign investment inflow increased positively according to price competitiveness, infrastructure quality, and natural resources. One development variable, information, and communication technology readiness, becomes significant when the analysis is performed only on developing countries. Economic risks, societal risks, technological risks, health and hygiene, human resources, and international openness are not significantly affecting investment inflow. An insightful theoretical implication regarding the finding is that some supports exist for the pollution haven hypothesis. Implications for practice include creating supportive policies that appreciate sustainable practices, such that investors are attracted to the country not as opportunistic polluters but as sustainability pioneers.